2011
DOI: 10.1074/jbc.m110.197988
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Thiol/Disulfide Redox Systems of the Anaerobe Desulfovibrio vulgaris Points Out Pyruvate:Ferredoxin Oxidoreductase as a New Target for Thioredoxin 1

Abstract: Sulfate reducers have developed a multifaceted adaptative strategy to survive against oxidative stresses. Along with this oxidative stress response, we recently characterized an elegant reversible disulfide bond-dependent protective mechanism in the pyruvate:ferredoxin oxidoreductase (PFOR) of various Desulfovibrio species. Here, we searched for thiol redox systems involved in this mechanism. Using thiol fluorescent labeling, we show that glutathione is not the major thiol/disulfide balancecontrolling compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 63 publications
2
48
0
Order By: Relevance
“…However, their relationships with the phylogenetically nearest neighbors suggested that the TrxRs of the Unknown I group are likely to be NTRs. The T. maritima TrxR that can use both NADH and NADPH (16) belonged to an NTR group containing bona fide enzymes from D. vulgaris (D.vulgaris_2, accession number AAS94860) (6) and Methanosarcina acetivorans (accession number, AAM04784) (9).…”
Section: Distribution and Phylogenetic Clades Of Dftr Homologsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their relationships with the phylogenetically nearest neighbors suggested that the TrxRs of the Unknown I group are likely to be NTRs. The T. maritima TrxR that can use both NADH and NADPH (16) belonged to an NTR group containing bona fide enzymes from D. vulgaris (D.vulgaris_2, accession number AAS94860) (6) and Methanosarcina acetivorans (accession number, AAM04784) (9).…”
Section: Distribution and Phylogenetic Clades Of Dftr Homologsmentioning
confidence: 99%
“…For example, the isolation of the putative Trx targets via Trxaffinity chromatography and the results from activation assays with select purified and deactivated enzymes have established that in Chlorobaculum tepidum, a green sulfur bacterium and an anaerobic phototroph, the thioredoxin system implements post-translational control on the tricarboxylic acid or the TCA cycle and sulfur metabolism and assists in the defense against oxidative stress (7). An analysis of mutant phenotypes and a gene expression study have revealed the critical roles of Trxs and TrxRs in the redox homeostasis and survival during oxidative stress in Bacteroides fragilis and Desulfovibrio vulgaris Hildenborough, respectively (6,14). Work with Clostridium pasteurianum, an anaerobic fermentative bacterium, has revealed a ferredoxin-dependent flavin containing TrxR (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Desulfovibrio vulgaris Hildenborough, a Gram-negative sulfate-reducing bacteria, two cytoplasmic thioredoxin systems have been identified (14). The Trx1/TR1 system contains the ubiquitous thioredoxin with the active site consensus sequence WCGPC.…”
mentioning
confidence: 99%
“…The Trx1/TR1 system contains the ubiquitous thioredoxin with the active site consensus sequence WCGPC. The second system contains an atypical thioredoxin with a CPHC sequence at the active site identical to the DsbA motif and an unconventional thioredoxin reductase that uses preferentially NADH (14). The presence of these atypical proteins being restricted to Desulfovibrio organisms, they have been named desulfothioredoxin (Dtrx) and desulfothioredoxin reductase (15).…”
mentioning
confidence: 99%